Can AI Predict Epileptic Seizures? A Deep Dive into Digital Health's Frontier - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Epilepsy, a chronic neurological disorder affecting over 50 million people globally 1, is characterized by the unpredictable nature of its seizures, which si...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Machine Learning; Wearable Technology